Psychometric properties of patient-reported outcome measures to assess premenstrual syndrome/premenstrual dysphoric disorder in japanese: a systematic review using the COSMIN methodology - Kaori Tsuyuki; Miho Egawa; Takuma Ohsuga; Yumie Ikeda; Yoshitake Takebayashi; Hideki Sato; Masaki Mandai (Journal of Patient-Reported Outcomes)
Abstract Background Patient-reported outcome measures (PROMs) are important for assessing premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) to effectively capture subjective symptom burden and evaluate treatment effectiveness in clinical and research settings. This systematic review evaluated the psychometric properties of PROMs used to assess PMS/PMDD in Japan. Methodology A systematic literature search was conducted in the MEDLINE, CINAHL, Cochrane Library, and Ichushi-Web databases. The COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) methodology was used to assess the methodological quality and measurement properties of the included PROMs. Results A total of 13 studies that evaluated 12 versions of 11 unique PROMs were included. PROMs were categorized as recall-based (n = 9, 69%) or daily recording scales (n = 4, 31%). The structural validity and internal consistency were relatively well evaluated for most scales. However, evidence was limited for other measurement properties such as reliability, criterion validity, and construct validity. None of the scales reported all psychometric properties outlined by COSMIN. The New Short-Form of the Premenstrual Symptoms Questionnaire and the Japanese version of the Daily Record of Severity of Problems demonstrated sufficient structural validity and internal consistency, although the quality of evidence for other properties was indeterminate. Conclusions Although some PROMs demonstrated promising psychometric properties, further validation studies are required for most scales. The development of innovative scales with robust measurement properties is essential for advancing the assessment of PMS/PMDD in Japanese clinical and research settings. Careful consideration of the characteristics of each PROM is necessary when selecting instruments for specific purposes.